2021
DOI: 10.3390/biology10030234
|View full text |Cite
|
Sign up to set email alerts
|

E3 Ubiquitin Ligase ASB17 Promotes Apoptosis by Ubiquitylating and Degrading BCLW and MCL1

Abstract: Apoptosis is a very important process of cell death controlled by multiple genes during which cells undergo certain events before dying. Apoptosis helps to clean the unnecessary cells and has critical physiological significance. Altered apoptosis results in a disorder of cell death and is associated with many diseases such as neurodegenerative diseases and cancers. Here, we reported that the ankyrin repeat and SOCS box protein 17 (ASB17) was mainly expressed in the testis and promoted apoptosis both in vivo an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“…In line with previous findings (24), Asb17-KO mice were viable, and fertility tests revealed normal fertility in Asb17-KO adult males, compared with WT or heterozygous (+/−) mice (Figure 2A). The testes weight was comparable between Asb17-KO and WT mice (Figure 2B,2C).…”
Section: Asb17 −/− Mice Are Fertilesupporting
confidence: 92%
See 3 more Smart Citations
“…In line with previous findings (24), Asb17-KO mice were viable, and fertility tests revealed normal fertility in Asb17-KO adult males, compared with WT or heterozygous (+/−) mice (Figure 2A). The testes weight was comparable between Asb17-KO and WT mice (Figure 2B,2C).…”
Section: Asb17 −/− Mice Are Fertilesupporting
confidence: 92%
“…In addition to the known roles of ASB17 in promoting spermatogenic cell apoptosis (24), in the present study, we uncovered a novel mechanism in spermiation involving ASB17-mediated ubiquitination and degradation of the ES associated protein, ESPN. Consistent with the previous work (24), we found that Asb17-KO males were fertile and showed complete spermatogenesis. However, we also showed that Asb17-KO males exhibited oligozoospermia, which was considered to be a major result of spermiation failure found in Asb17-KO.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…It should be noted that the delicate balance between anti-and proapoptotic proteins of the Bcl-2 family determines the life and death decisions of cells. This balance is influenced by several factors, including interaction, localization, expression level, half-life, and PTM of Bcl-2 proteins [83,[216][217][218][219][220]. During different stages of tumorigenesis and metastasis, cancer cells evade apoptosis by modulating Bcl-2 protein family members, such as by the upregulation of antiapoptotic Bcl-2 proteins and the downregulation or removal of proapoptotic Bcl-2 members [221].…”
Section: Apoptosis In Human Diseasesmentioning
confidence: 99%